High-precision mass measurements for the isobaric multiplet mass equation at A = 52. (19th April 2017) - Nesterenko, D A; Kankainen, A; Canete, L; Block, M; Cox, D; Eronen, T; Fahlander, C; Forsberg, U; Gerl, J; Golubev, P; Hakala, J; Jokinen, A; et al.
Abstract: Masses of 52 Co, 52 Co m, 52 Fe, 52 Fe m, and 52 Mn have been measured with the JYFLTRAP double Penning trap mass spectrometer. The isobaric multiplet mass equation for the T = 2 quintet at A = 52 has been studied employing the new mass values. No significant breakdown (beyond the 3 σ level) of the quadratic form of the IMME was observed ( χ 2 / n = 2.4 ). The cubic coefficient was 6.0(32) keV ( χ 2 / n = 1.1 ). The excitation energies for the isomer and the T = 2 isobaric analog state in 52 Co have been determined to be 374(13) keV and 2922(13) keV, respectively. The measured mass values for 52 Co and 52 Co m are 29(10) keV and 16(15) keV higher, respectively, than obtained in a recent storage-ring experiment, and significantly lower than predicted by extrapolations. Consequently, this has an impact on the proton separation energies for 52 Co and 53 Ni relevant for the astrophysical rapid proton capture process. The Q value for the proton decay from the 19 / 2 − isomer in 53 Co has been determined with an unprecedented precision, Q p = 1558.8 ( 17 ) keV.